Al-Farabi and the question on existence - Pour Hasan, Ghasem (Journal of Oriental Studies, 2020)
Farabi’s (also Al Farabi) fundamental question is the question of existence. Metaphysics, physics, ethics, politics and civil science of Farabi can be understood and evaluated within the problem of existence. Exploration of the meaning of existence has overshadowed his whole philosophy. Farabi must be seen as the systematic beginning of Islamic Philosophy not as its fountain-head. Farabi owes his own ontological system more to the religious teachings, Islamic culture and thought and Iranian wisdom, heritage and tradition. Precisely speaking, main and true origin of Islamic philosophy is not Greece rather Quranic verses and prophetic traditions as well as prayers and scriptural texts. Emergence or uncovered-ness of existence in Farabi becomes connected with thinking. Wherever there is no thinking, existence will be in covered-ness or hiddenness. In search of the meaning of existence, Farabi does not ask of its quiddity (what-is-it-ness). Question of quiddity of existence is basically wrong and makes one to get stuck in the swamp of verbalism and more dangerous than it, turns the existence into an object. Existence is not separated from thinking. Existence is not an object along with other objects in the outside world so that we can ask of its nature or quiddity. Existence is of uncovered-ness (Unverborgenheit) only within the horizon of thinking. Question of quiddity or what-is-it-ness of existence is tantamount to its forgetfulness and covered-ness. Has Farabi had any innovation in the domain of ontological issues that would make him distinguished by us as compared to his predecessors? Does he speak of a type of novel ontology that can serve as an alternative to the existing ones? What are differences between his philosophy and those of Plato and Aristotle? Are we encountered with different definitions, types of notions, categories or approaches in Farabi? If there are such inventions, would they be to the extent that could they lead to the establishment of a system within the sphere of ontology? Examination of these questions shows that Farabi has a distinguished concern in philosophy different from those of the Greek philosophers. Religious teachings, paying attention to the role and influence of oriental wisdom or Sophia Iranica in philosophical thinking, search for true wisdom and separation from Greek notions and finally providing a theory of synthesis and reconciliation of religion and philosophy constitute Farabi’s main approach. Key words: Farabi, Existence, Epistemic Detachment, Greek Tradition, Aristotle.